2013
DOI: 10.7771/1541-5015.1325
|View full text |Cite
|
Sign up to set email alerts
|

Building On and Honoring Forty Years of PBL Scholarship from Howard Barrows: A Scientometric, Large-Scale Data, and Visualization-based Analysis

Abstract: Over the past forty years, Howard Barrows' contributions to PBL research have influenced and guided educational research and practice in a diversity of domains. It is necessary to make visible to all PBL scholars what has been accomplished, what is perceived as significant, and what is the scope of applicability for Barrows' groundbreaking findings. As more disciplines recognize Barrows' efforts and adopt PBL in education, it becomes crucial but challenging to sustain community memory so that PBL scholars are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Despite pronounced progress on the application and research regarding PBL, no bibliometric studies in the literature that examine scientific production on the subject on a broad time scale are available, with the exception of one bibliometric analysis by Xian and Madhavan (2013) regarding the contribution of Howard Barrows to PBL research. Barrows was an American physician who for over forty years has been a leading researcher and propagator on the use of PBL in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…Despite pronounced progress on the application and research regarding PBL, no bibliometric studies in the literature that examine scientific production on the subject on a broad time scale are available, with the exception of one bibliometric analysis by Xian and Madhavan (2013) regarding the contribution of Howard Barrows to PBL research. Barrows was an American physician who for over forty years has been a leading researcher and propagator on the use of PBL in medical education.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted at the outset that this review was designed to extend findings reported in prior bibliometric reviews of the PBL literature. These bibliometric reviews employed citation analysis to identify high-impact authors (Xian andMadhavan, 1436 P. Hallinger 2013;Pinho et al, 2015) and documents (Azer, 2017) in the PBL literature. For example, using citation analysis of a much smaller database, Pinho et al (2015) identified Barrows, Schmidt, Norman, Hmelo-Silver, van der Vleuten, Dolmans and Sherpbier as thought leaders in the PBL literature.…”
Section: Interpretation and Implications Of The Findingsmentioning
confidence: 99%
“…The motivation to adopt PBL in medical education arose from perceived inadequacies of traditional teacherā€centred instruction, which yielded poor results with respect to student retention and transfer of medical knowledge and skills (Schmidt, 1983). While early adoption of PBL was concentrated in medical education during the 1980s, the use of PBL gradually spread to other fields of professional and Kā€12 education in subsequent decades (Xian and Madhavan, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two possible explanations for this variability are the discrepancies in implementation and problem type (Walker & Leary, 2009). Another explanation is the lack of consensus in definitions of PBL (Xian & Madhavan, 2013). While multiple scholars have advocated for considering PBL as a "genus for which there are many species and subspecies" (Barrows, 1986, p. 485), the scholarly community is still lacking a depth of understanding in how PBL is defined and implemented in different disciplines (Xian & Madhavan, 2013).…”
Section: Introductionmentioning
confidence: 99%